The application of philosophical tools to the theme of relativity and relativism - Visagie, Johann (University of the Free State, 2005)
English: This article initially describes a specific conception of philosophical tools — models of coherence at various levels and in different contexts of philosophical analysis. The overall purpose is to apply some of these tools to the theme of relativity and relativism. The first tool tested in this way will be the key formulas of philosophical discourse, with special reference to Derrida and deconstruction. Then the perspectives offered on the theme by various other tools will be explored. The article concludes with some remarks on spirituality and relativity, as well as the possibility of a future relativity.

Afrikaans: In hierdie artikel word ’n spesifieke konsepsie van filosofiese denkgereedskap beskryf, naamlik modelle van samehang op verskillende vlakke en in verskillende kontekste van filosofiese analise. Die oorkoepelende doelwit is die toepassing van hierdie ge- reedskap op die tema van relatiwiteit en relativisme. Die eerste instrument wat so getoets word, is die sleutelformules van filosofiese diskoers, met spesiale verwysing na Derrida en dekonstruksie. Vervolgens word verskeie ander analitiese instrumente aan die orde gestel. Die artikel sluit met opmerkings oor relatiwiteit en spiritualiteit, sowel as die moontlikheid van ’n toekomstige relatiwiteit waarna ons kan uitsien.
Keywords: Philosophy; Relativism; Relativity; Derrida